THE INFLUENCE OF AVAILABILITY AND PROMOTION ON CUSTOMER RETENTION WITH THE CUSTOMER SATISFACTION AS A MEDIATING VARIABLE – A LITERATURE REVIEW ON THE PERSONAL CARE INDUSTRY - Tjoeanda, Christopher Andrew; Hartono, Markus (J@ti Undip: Jurnal Teknik Industri, 2026)
The personal care industry relies on product innovation, distribution, and promotional strategies as key factors for business success. Product availability and effective promotion play crucial roles in customer satisfaction and retention. However, limited research discusses how these two aspects interact and affect business sustainability in the personal care industry. To address this gap, this literature examines how prior studies have conceptualized and examined the relationships among product availability, promotion, customer satisfaction, and customer retention within the personal care industry. Relevant studies from marketing and distribution were systematically reviewed, using publications collected from ScienceDirect. We initially gathered 3,491 articles related to personal care, restricted to the last ten years, classified as research articles, and aligned with keywords such as marketing, promotion, advertising, discounting, branding, product completeness, and product availability. From this process, ten key journal articles were selected for further analysis. The findings reveal that product availability enhances customer satisfaction and encourages repeat purchases, while promotional strategies foster positive product perceptions and strengthen brand awareness. Together, these strategies provide a cohesive approach that significantly impacts customer retention. Overall, this study highlights the importance of combining product availability and promotional efforts to improve customer experience and support long-term success in the personal care industry. However, this study is limited to a conceptual framework and does not yet test the proposed relationships empirically. Future research is recommended to validate this structural model through application in real-world cases within the personal care industry, which would provide stronger practical insights and implications for both academics and practitioners.